Predictors of echocardiographic response in the Budapest-CRT upgrade trial - Eperke Merkel; Richárd Masszi; Bálint Lakatos; Robert Hatala; Boglárka Veres; Alexandra Fábián; István Osztheimer; László Gellér; Tamás Urbán; Csaba Horváth; Scott D. Solomon; Valentina Kutyifa; et al. (Clinical Research in Cardiology, 2026)
Abstract Background and aims Up to 30% of patients fail to respond after cardiac resynchronization therapy (CRT). While echocardiographic predictors of response are well described in de novo CRT, evidence in CRT upgrade populations remains limited. We investigated predictors of echocardiographic response in the BUDAPEST-CRT Upgrade trial cohort. Methods In this randomized trial, 360 patients with heart failure and reduced ejection fraction (HFrEF) with priorly implanted pacemaker or ICD, ≥ 20% right ventricular (RV) pacing burden, and wide-paced QRS (≥ 150 ms) were randomized to CRT-D upgrade ( n = 215) or ICD upgrade ( n = 145). Echocardiographic response was defined as ≥ 15% reduction in left ventricular end-systolic volume (LVESV) at 12 months. Results Among 275 patients with paired echocardiographic data, 161 (59%) were responders. Responders had fewer HF hospitalizations (0.6% vs. 7.0%, p = 0.003), more often received mineralocorticoid receptor antagonists (71% vs. 59%, p = 0.038), and showed a higher baseline RV pacing burden (88.9% vs. 83.4%, p = 0.025) than non-responders. Independent predictors of echocardiographic response were randomization to CRT-D (OR 5.57, 95% CI 2.56–12.12, p < 0.0001), greater RV pacing burden (OR 1.02 per %, 95% CI 1.00–1.04, p = 0.024), non-ischemic cardiomyopathy (OR 2.50, 95% CI 1.15–5.26, p = 0.021), and a lateral LV lead position (OR 8.79, 95% CI 1.28–60.39, p = 0.027). Conclusions In patients with pacing-induced cardiomyopathy, CRT-D upgrade significantly improved echocardiographic outcomes. Non-ischemic etiology, higher RV pacing burden, and lateral LV lead positioning were associated with greater benefit. These results underscore the importance of tailored patient selection and lead placement strategies to optimize CRT-D upgrade outcomes.